Comparative Study Between Different Methods of Insemination in Iraqi Does: HA AL-Mutar ,AF Alwan ,MJ Eesa ,NS Ibrahem HF Kashifalkitaa - AL-Mutar, HA . (The Iraqi Journal of Veterinary Medicine, 2011)
Present experimental was carried out on 22 does 2-4 years old. The aim was to induction of estrous in non-breeding season using impregnated sponge with 20 mg of medroxy progesterone acetate (MPA) for 13 days and with an i/m injection of 500 IU Pregnant Mare Serum Gonadotropin (PMSG) hormone 24 hrs before sponge withdrawal and to compare the pregnancy rate using three different methods of insemination; natural , cervical and laparoscopic artificial insemination at fixed time 24-48 hrs after estrous onset. All does were showed signs of estrous (100%), the estrous time was 46.9±4.90hrs (24-60hrs) after sponge withdrawal. While estrous length was 37.09±1.91 (24–72hrs). All experimental animals followed up by abdominal palpation, ultrasonography at 30, 60 and 90 days post-insemination, while the laparoscopic examination was performed at day 30 post-insemination, to improve the efficiently of the different methods of inseminations in pregnancy rate ultrasonographical diagnosed by rectal and abdominal methods of 14 does post-inseminations appeared that two were pregnant, seven suspected and five non pregnant. At day 60th , post-insemination the pregnancy diagnosis of (22) does appeared that (14) were pregnant, six suspected and two non pregnant. While at day 90, the examination of all does appeared that (16) animals were pregnant and six were not. The laparoscopic examination, at 30 days post-insemination showed that eight does were pregnant, two suspected and two were not pregnant. In conclusion that the pregnancy rate of laparoscopic insemination is (75%), comparisons to natural (66.7%) and cervical AI method (75%) but there is no significant different between them, while the kidding percentage was appear in natural insemination (75%), cervical (100%) and laparoscopic insemination (150%). The results of this study indicate that estrus can be efficiently induced in female goats during non-breeding season using 20mg MPA impregnated spongewith 500IU PMSG.